Synthesis, Characterization and applications of Some New 5-Substituted-4-Thiazolidinone-2-Thioxo Azo Derivatives - Bajpai, Rita; Tiwari, Sanjay; Tiwari, K.S.; Tiwari, B.M.L. (Asian Journal of Chemistry, 2010)
4-Thiazolidinone-2-thioxo (I) has been refluxed separately with untried phenylazo-salicylaldehydes to get some new chelating 5-substituted-4-thiazolidinone-2-thioxo azo derivatives (II-V). For comparison the 5-(salicylidene) derivative (VI) has also been explored. Their characterisation has been done by chemical and spectral data. The azo derivatives (II-V) have been used in dyeing a variety of fabrics and histological staining. The derivatives (II-VI) have shown distinctive antimicrobial activity as antibacterial, antifungal and antitubercular; and are capable of acting as specific spot test and chromatographic spray reagents. Their toxicity effect and insecticidal activity have been determined with respect to mortality of mosquito larvae, culex and anopheles sp.